Game location effect in the NBA: A comparative analysis of playing at home, away and in a neutral court during the COVID-19 season - Bustamante-Sanchez, A.; Gomez, M. A.; Jimenez-Saiz, S. L. (International Journal of Performance Analysis in Sport, 2022)
The home advantage effect seems to be related to a more functional aggressive behaviour with an increased performance in rebounds. It has been traditionally considered as an important factor during basketball games that needs to be studied under different scenarios (home, away or neutral locations). This study aimed to analyse NBA team`s game-related statistics, pre-shooting combinations and pick-and-roll performances among locations (playing at home, away and in a neutral court) during the COVID-19 season. A retrospective cross-sectional study of the 2019-2020 NBA season (906 games) was carried out. Game-related statistics were gathered from the private company InStat (https://basketball.instatscout.com/). The main results showedthat (i) home-court teams had better performances in points, field goal percentage, rebounds, assists and fouls than away-court teams and neutral-court teams; (ii) home-court teams had better performances than away-court teams or neutral-court teams in transitions and cuts made and (iii) home-court teams and neutral-court teams had similar performances to away-court teams in pick-and-roll and pick-and-pop situations although teams playing away had more attempts. In conclusion, playing at home under different circumstances favours the local team, mainly using a more collective way of play.